Capital Income Taxation of Asymmetric Countries - Michael J. Koop (Kiel Institute of World Economics (IfW), 2001)
The paper analyzes the effects of a source-based capital income tax on production and market structures, trade and capital flows as well as national and global welfare. The analysis is carried by means of a general equilibrium model of trade which incorporates international capital flows as well as the existence of multinational enterprises. The focus of the paper is on identifying the influence of different absolute and relative factor endowments on the effects of capital income taxation. Simulations of the model show that a one-size-fits-all tax policy does not exist and that governments need to take their own country's factor endowment into account when making tax policy decisions.
Keywords: D52; H24; H21; H43; 330; Capital Income Taxation; Asymmetric Countries; Capital Mobility; Tax Competition; Kapitalertragsteuer; Steuerwettbewerb; Steuerwirkung; Aussenwirtschaftstheorie; Direktinvestition; Multinationales Unternehmen; Allgemeines Gleichgewicht; Internationale Kapitalmobilität; Wohlfahrtseffekt; Faktorproportionentheorem; Theorie